(untitled) (Archives of Mechanics - Test, 2010)
The paper discusses theoretical fundamentals necessary for accurate vibroacoustical modeling of structures or composites made up of poroelastic, elastic, and (active) piezoelectric materials, immersed in an acoustic medium (e.g. air). An accuratemodeling of such hybrid active-passive vibroacoustic attenuators (absorbers or insulators) requires a multiphysics approach involving the finite element method to cope with complex geometries. Such fully-coupled, multiphysics model is given in this paper. To this end, first, the accurate PDE-based models of all the involved single-physics problems are recalled and, since a mutual interaction of these various problems is of the uttermost importance, the relevant couplings are thoroughly investigated and taken into account in the modeling. Eventually, the Galerkin finite element model is developed. This model should serve to develop designs of active composite vibroacoustic attenuators made up of porous foams with passive and active solid implants, or hybrid liners and panels made up of a core or layers of porous materials fixed to elastic faceplates with piezoelectric actuators, and coupled to air-gaps. A widespread design of such smart mufflers is still an open topic and should be addressed with accurate predictive tools based on the model proposed in the present paper. The model is accurate in the framework of kinematical and constitutive (material) linearity of behaviour. This is, however, the very case of the vibroacoustic application of elasto-poroelastic panels or composites, where the structural vibrations are induced by acoustic waves. The developed fully-coupled FE model is finally used to solve a generic two-dimensional example and some issues concerning finite element approximation and convergence are also discussed.